The Effect of Word of Mouth and Promotion on Purchasing Decisions for Alauddin Makassar Branch Fore Products - Santy, Raeni Dwi; Nur DJ, Arini Izzatan; Rostini; Zhalila, Annisa; Syahribulan (PT. Maju Malaqbi Makkarana, 2025)
This study aims to determine the effect of Word of Mouth (WOM) and promotion on consumer purchasing decisions for Fore Coffee products at the Alauddin Makassar branch. In the current digital era, consumer behavior is heavily influenced by peer recommendations and digital promotional strategies. Using a quantitative research approach with stratified random sampling, data were collected from 100 respondents through a Likert-scale questionnaire. Multiple linear regression analysis was used to assess the impact of the two independent variables—WOM and promotion—on purchasing decisions. The results showed that WOM has a significant partial influence on purchasing decisions, indicating that peer communication, both traditional and electronic, is a dominant factor in shaping consumer perceptions and preferences. Promotion, on the other hand, did not show a significant partial effect, suggesting that price incentives alone may not be sufficient to influence purchasing behavior unless reinforced by social influence or trust. However, the simultaneous effect of WOM and promotion was statistically significant, emphasizing their combined role in consumer decision-making. The study concludes that WOM is a more dominant and effective marketing tool than standalone promotions and should be central to marketing strategies in the lifestyle-based coffee industry. These findings contribute to a deeper understanding of consumer behavior and offer practical implications for enhancing marketing effectiveness through integrated communication approaches.